Identification of Students' Mathematical Creative Thinking Ability in Number Pattern Problems Solving - Ivan Hartaji; Isbadar Nursit; Abdul Halim Fathani; Yula Milshteyn (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Improving the learning mathematics process in the classroom requires creative thinking skills. In learning mathematics, creative thinking skill is one of the critical mathematical skills to be mastered and developed by students. Creative thinking adds support to students so that students are more enthusiastic about problem-solving. Creative thinking is exploring different, quality, and task-appropriate ideas. The research aims to describe students' mathematical creative thinking skills in number patterns for the eighth grade of MTs Mamba'ul Ulum Pandaan. This research approach was qualitative. The qualitative design was descriptive qualitative. The data collection process was carried out at MTs Mamba'ul Ulum Pandaan. Data collection techniques were carried out in three ways: observation, tests, and interviews. After the data was obtained, qualitative data analysis was then carried out, which consisted of pre-field analysis and field analysis. Field analysis consisted of data reduction, data presentation, and conclusion. Then, the validity of the data was tested. The study results indicated that students with high mathematical creative thinking skills met four indicators. Students with moderate creative thinking skills met two indicators, while those with low creative thinking skills did not meet any predetermined indicators.